Management and treatment of myocarditis in athletes - Hurwitz, B.; Issa, O. (Current Treatment Options in Cardiovascular Medicine, 2020)
Purpose of review: Myocarditis is an inflammation of the myocardium that can often be associated with cardiac dysfunction and arrhythmias, and is even one of the leading causes for sudden cardiac death (SCD) in athletes. This review aims to summarize the current evidence and treatment guidelines for the management of myocarditis in the active population.